2009
DOI: 10.3892/or_00000310
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human papillomavirus and Epstein-Barr virus in lung adenocarcinoma

Lim

Abstract: Abstract. The association of human papillomavirus (HPV) and Epstein-Barr virus (EBV) infection with non-small cell lung cancer is controversial. HPV and EBV prevalence in a uniform population of lung adenocarcinoma was investigated, hypothesizing that there would be differences seen between smokers and non-smokers and between sexes. Patients involved in this study were selected from a single institution database of lung cancer. In total 497 patients with adenocarcinoma were identified and 110 patients had suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
0
24
1
1
Order By: Relevance
“…Results based on in situ hybridization suggest that PCR-based analysis may vastly overestimate the frequency and relevance of HPV in primary lung cancers. Lim et al were unable to detect any HPV-positivity among 110 primary lung adenocarcinomas,(26) and we did not detect HPV among a broader range of primary lung carcinomas types including SqCCs with the basaloid phenotype ā€“ a phenotype that is commonly associated with HPV infection in non-pulmonary sites including the oropharynx, vulva, penis and anus. (6,11,13,21)…”
Section: Discussioncontrasting
confidence: 50%
“…Results based on in situ hybridization suggest that PCR-based analysis may vastly overestimate the frequency and relevance of HPV in primary lung cancers. Lim et al were unable to detect any HPV-positivity among 110 primary lung adenocarcinomas,(26) and we did not detect HPV among a broader range of primary lung carcinomas types including SqCCs with the basaloid phenotype ā€“ a phenotype that is commonly associated with HPV infection in non-pulmonary sites including the oropharynx, vulva, penis and anus. (6,11,13,21)…”
Section: Discussioncontrasting
confidence: 50%
“…Two previous serologic studies found a higher seroprevalence of several EBV antibodies in lung cancer cases compared with healthy controls (Desgranges and de-The, 1979; Roy et al , 1994). Among tissue-based studies, some studies have found 5ā€“10% positivity by EBER ISH or EBV nuclear antigen IHC (Kasai et al , 1994; Wong et al , 1995; Grinstein et al , 2002), whereas others have found no positivity by EBER ISH (Conway et al , 1996; Kijima et al , 2001; Hayakawa et al , 2003; Chu et al , 2004; Lim et al , 2009) and generally low or no positivity by other markers (Chu et al , 2004). Although EBER ISH is considered the gold standard for detecting EBV-associated cancers because of its high abundance in latently EBV-infected cells, it is not a perfect measure (Delecluse et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been implicated in āˆ¼10% of gastric cancers (Young and Rickinson, 2004). Although lung cancer cases in serological studies had higher EBV seropositivity than healthy controls (Desgranges and de-The, 1979; Roy et al , 1994), previous studies of EBV in lung tumour tissue have generally produced negative results, except in rare cases of lymphoepithelioma-like carcinomas (LELCs) (Chu et al , 2004; Lim et al , 2009). However, previous studies largely tested for expression of EBV-encoded small RNA ( EBER ), which is generally abundantly expressed in cells with latent EBV infection but occasionally may be absent or heterogeneously expressed in EBV DNA-positive tumours (Iwakiri and Takada, 2010).…”
mentioning
confidence: 99%
“…In Taiwan, EBV is the most important etiological factor for NPC; circulating EBV DNA levels are positively correlated with disease stage and prognosis (Lin et al 2001;Lin et al 2004). On the other hand, EBV is not an etiological agent in lung or esophageal cancer (Lim et al 2009;Sunpaweravong et al 2005;Yanai et al 2003). The exclusive role of EBV in the pathogenesis might explain the distinct patterns of second primaries in NPC (Chen et al 2008).…”
Section: Discussionmentioning
confidence: 95%